2004
DOI: 10.1177/0269881104042618
|View full text |Cite
|
Sign up to set email alerts
|

QTc Interval, CYP2D6 and CYP2C9 Genotypes and Risperidone Plasma Concentrations

Abstract: The role of certain drug metabolizing enzymes in cardiotoxicity, such as CYP2D6 for thioridazine, has been suggested. Risperidone has been shown to inhibit the delayed rectifier leading to lengthening of cardiac repolarization. The heart-rate corrected QT (QTc) interval lengthening has been reported in psychiatric patients receiving risperidone under steady-state conditions. CYP2D6 is involved in the metabolism of risperidone to 9-hydroxy (OH)-risperidone. CYP2C9 enzyme is also involved in the metabolism of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 30 publications
1
38
1
Order By: Relevance
“…In particular, a risperidone or venlafaxine result suggesting a PM genotype should serve as an indication for additional TDM to guide the dosing of other coprescribed drug substrates of CYP2D6 so as to avoid the risk of adverse drug reactions as reported in several clinical settings. [2][3][4][5][6][7] Thus, genetically deficient CYP2D6 metabolism has been associated with adverse drug reactions in patients treated with CYP2D6-dependent antidepressants, 2 with a greater length of hospitalization for different groups of psychiatric patients, 4,5 with prolonged QTc interval in patients on risperidone, 3 and with extrapyramidal syndrome or tardive dyskinesia in patients taking antipsychotic drugs in general. 6,7 Importantly, such a strategy would also avoid therapeutic failure with regard to prodrugs, ie, drugs whose therapeutic effect is dependent on a pharmacologic active metabolite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a risperidone or venlafaxine result suggesting a PM genotype should serve as an indication for additional TDM to guide the dosing of other coprescribed drug substrates of CYP2D6 so as to avoid the risk of adverse drug reactions as reported in several clinical settings. [2][3][4][5][6][7] Thus, genetically deficient CYP2D6 metabolism has been associated with adverse drug reactions in patients treated with CYP2D6-dependent antidepressants, 2 with a greater length of hospitalization for different groups of psychiatric patients, 4,5 with prolonged QTc interval in patients on risperidone, 3 and with extrapyramidal syndrome or tardive dyskinesia in patients taking antipsychotic drugs in general. 6,7 Importantly, such a strategy would also avoid therapeutic failure with regard to prodrugs, ie, drugs whose therapeutic effect is dependent on a pharmacologic active metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Different genetic variants of CYP2D6 indeed contribute to marked interpatient variability in their pharmacokinetics, 1 with a well established impact on the clinical outcome and, in particular, the risk of adverse events with regard to drugs metabolized by this enzyme. [2][3][4][5][6][7] However, in most institutions, CYP2D6 genotyping has not been adopted into routine clinical practice, instead it has been restricted to retrospective analyses in selected cases. 8 Knowledge of the individual CYP2D6 activity, or more specifically the poor metabolizer (PM) or ultrarapid metabolizer (UM) genotype, is of potential importance regarding ongoing and future drug treatment in patients with many antidepressants and antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…QTc was calculated from QT/RR k , with constant k derived from the slope of the regression of lnQTc on lnRR, from pooled baseline data. Another study in 27 patients (percentage of female not given, age 19-76 years), with no indication of how QTc was calculated, found a QTc > 420 ms in 11% of patients on a mean dosage of 5.4 ± 2.9 mg risperidone (Llerena et al, 2004). The QTc interval was longer among those individuals carrying one CYP2D6 active gene compared to those with two.…”
Section: Risperidonementioning
confidence: 99%
“…1 It is known that CYP2D6 is involved in the metabolism of several psychotropic drugs, 2 and we have shown it to influence the plasma concentration of antipsychotics (haloperidol, thioridazine, risperidone and so on) and their relevance for QTc interval lengthening. [3][4][5][6][7] The expression of CYP2D6 enzyme has been described not only in the liver but also in other tissues such as the brain, where it is localized in the pyramidal cells of the cortex and hippocampus (CA1-3) and the Purkinje cells of the cerebellum. 8,9 CYP2D6 activity has also been related to personality traits (psychic anxiety, psychasthaenia, inhibition of aggression, and socialization), which suggested that CYP2D6 enzyme may have an endogenous neuroactive substrate or product, such as a biogenic neurotransmitter amine.…”
Section: Introductionmentioning
confidence: 99%